2021
DOI: 10.1038/s41598-021-94147-y
|View full text |Cite
|
Sign up to set email alerts
|

Spherulitic and rotational crystal growth of Quartz thin films

Abstract: To obtain crystalline thin films of alpha-Quartz represents a challenge due to the tendency for the material towards spherulitic growth. Thus, understanding the mechanisms that give rise to spherulitic growth can help regulate the growth process. Here the spherulitic type of 2D crystal growth in thin amorphous Quartz films was analyzed by electron back-scatter diffraction (EBSD). EBSD was used to measure the size, orientation, and rotation of crystallographic grains in polycrystalline SiO2 and GeO2 thin films … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…On the contrary, for the thin films on sapphire substrates, an additional nucleation barrier is present. Our recent study on thin films on sapphire substrates has found that the nucleation starts from the top surface of the thin film 51 . Thus, the growth front at the film top is advanced with respect to the growth front at the film bottom, leading to rotation of the lattice during the growth 51 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, for the thin films on sapphire substrates, an additional nucleation barrier is present. Our recent study on thin films on sapphire substrates has found that the nucleation starts from the top surface of the thin film 51 . Thus, the growth front at the film top is advanced with respect to the growth front at the film bottom, leading to rotation of the lattice during the growth 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study on thin films on sapphire substrates has found that the nucleation starts from the top surface of the thin film 51 . Thus, the growth front at the film top is advanced with respect to the growth front at the film bottom, leading to rotation of the lattice during the growth 51 . When the nucleation starts from the top, it loses the information from the substrate and results in randomly oriented crystals.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, for the Si x Ge 1−x O 2 thin films on sapphire substrates, an additional nucleation barrier is present. Our recent study on GeO 2 thin films on sapphire substrates has found that the nucleation starts from the top surface of the thin film 53 . Thus, the growth front at the film top is advanced with respect to the growth front at the film bottom, leading to rotation of the lattice during the growth 53 .…”
Section: Crystallization Mechanism Of Simentioning
confidence: 98%
“…Our recent study on GeO 2 thin films on sapphire substrates has found that the nucleation starts from the top surface of the thin film 53 . Thus, the growth front at the film top is advanced with respect to the growth front at the film bottom, leading to rotation of the lattice during the growth 53 . When the nucleation starts from the top, it loses the information from the substrate and results in randomly oriented crystals.…”
Section: Crystallization Mechanism Of Simentioning
confidence: 98%
“…10 Spherulitic growth has been observed in isothermally crystallized amorphous thin films and on glass surfaces by electron backscatter diffraction (EBSD), where confinement of growing crystal by glass offers desirable conditions. Amorphous thin films of SiO 2 1 and GeO 2 1 , 11 were shown to form α-quartz spherulites with gradual lattice bending along individual crystallites (Figure 1B). The authors noted that spherulitic growth occurred only at lower annealing temperatures, transitioning to dendritic and single crystal growth at higher temperatures presumably due to increased chemical mobilities.…”
Section: Lattice Engineering: Bending Twisting and Spherulitic Growthmentioning
confidence: 99%